Lessons learned from the experiences of informal PrEP users in France: results from the ANRS-PrEPage study. (20th June 2018) - Rivierez, I.; Quatremere, G.; Spire, B.; Ghosn, J.; Rojas Castro, D.
ABSTRACT: Before January 2016, Pre-Exposure Prophylaxis (PrEP), a new biomedical HIV-prevention tool, was only available in France via ANRS-Ipergay clinical study but informal use was reported outside this setting. PrEPage qualitative study reports profiles and experiences of participants who used PrEP outside of a biomedical trial before this prevention method was authorized. Between March 2015 and February 2016, a cross-section of twenty-four informal PrEP users, mostly MSM, was recruited to complete in-depth semi-structured interviews. While ANRS-Ipergay was still ongoing (2012–2016), participants described their initiation to PrEP, the way they used it and the difficulties they faced to acquire antiretroviral drugs in an environment where PrEP was still not widely known and often criticized. Through the testimonies, different user profiles and motivation toward informal PrEP use emerged: (a) participants who have increasing difficulties using condoms, (b) "opportunists" who tried PrEP without the intention of using it regularly and (c) participants with a risk aversion who sought additional protection against HIV. Participants chose to use PrEP and/or their usual prevention strategies depending on available supplies, type of partners and individual attitudes toward risk. The feeling of living a safer sex life helped participants to outweigh the fear of possible toxicity and drug resistance. Participants' needs and expectations about PrEP implementation in France were also presented.